Best’s disease – family case report - Kwiecień, Sława; Ulińska, Magdalena; Sulak, Robert; Szaflik, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Friedrich Best described in 1905 for the first time a genetic disease which is subject to autosomal dominant inheritance. Yellow material is assembled under pigment epithelium, especially in the macula. Afterwards pigment epithelium and choroid become involved in the process and visual acuity decreases. In the last phase the fibrotic scar appears in the macula with deterioration of visual acuity. In some late cases choroidal neovascularization develops too. We present a two-generation-family which suffers from Best’s disease. Our patients: mother, her daughter and her son demonstrate changes in different phases of development. In mother’s case we found fibrotic scar and atrophy of pigment epithelium, which is typical of the late phase of the disease. Daughter complained of decrease in visual acuity, the subretinal neovascularisation was found in the macula and photodynamic therapy was performed. Visual acuity improved from 0.5 to 0.8 and has been stable for 11 months. Son did not report any symptoms. Some yellow material was found under the macula in both eyes without decrease of visual acuity. Described case shows importance of the whole family members’ examination in case of Best’s disease. Early diagnosis of this serious disease makes possibility of proper treatment.